Broadcasting and national identity construction in Qatar: The case of Al-Rayyan TV. (1st November 2021) - Miladi, Noureddine; Ben Messaoud, Moez; Zran, Jamel
This research sought to study the contents of Al-Rayyan TV programmes and their relationship to the construction of national identity in Qatar, a task this channel has taken as an editorial line since its inception in 2012. In this article, we present findings of an audience-based exploration of Al-Rayyan TV's viewership. Fieldwork data was gathered via a base of 720 survey questionnaires from a sample of Qatari society as well as fifteen interviews conducted with experts and social media activists. The aim was to find out respondents' views about the role of the channel in promoting Qatari identity and culture. Research questionnaires were managed at intervals between August and November 2020. Fieldwork results showed that the surveyed viewers believe that the channel plays a significant role in preserving Qatari national culture and heritage. However, when it comes to rating Qatari TV channels in order of importance, respondents' favourite TV broadcaster in terms of news and current affairs programmes was Al Jazeera, followed by beIN Sports, Qatar TV, Al-Rayyan TV and finally Al Kass. Research findings also reveal an evident trend among young Qataris and professionals who find social media networks the most convenient platforms to view and share content from Al-Rayyan TV. People watch video clips from the most popular programmes, such as Al-Sabah Rabah, Umm Rashid, Taraheeb and In the Shadows of Doha, among others, which they receive via Twitter, Instagram and Facebook. However, concerns via-à-vis Al-Rayyan TV's repetitive content and a programme schedule that does not include much entertainment content cannot be missed from viewers' responses. The dwindling popularity of the channel among Qatari youth is perceived as one such result of its inability to transform itself in the age of digital explosion.